The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1159/000095860
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Acetazolamide and Apraclonidine in the Control of Intraocular Pressure following Phacoemulsification

Abstract: Purpose: The purpose of our study was to compare the effects of systemically administered acetazolamide and topical apraclonidine 0.5% in the control of intraocular pressure (IOP) following phacoemulsification of senile cataracts. Setting: The study was conducted on patients affected by cataract and followed at the Department of Ophthalmology. Methods: Seventy-eight eyes in 78 patients were selected. Twenty-six eyes were randomly assigned to postoperative treatment with topical apraclonidine 0.5%, 26 received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…In this study, the patients received the medication postoperative and every 8 hr until day 1 (Scuderi et al. ). Regarding dorzolamide, only one of the trials met the inclusion criteria, and presented data for 3–8 hr, with a relative effect of 28.0% and with high quality of evidence (Schwenn et al.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the patients received the medication postoperative and every 8 hr until day 1 (Scuderi et al. ). Regarding dorzolamide, only one of the trials met the inclusion criteria, and presented data for 3–8 hr, with a relative effect of 28.0% and with high quality of evidence (Schwenn et al.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between preoperative and postoperative IOP did not reflect a significant difference in the two groups (p = 0.3919, paired t-test) (Table 3). Three eyes received hypotensive treatment on the first postoperative day; two were treated with topical apraclonidine 0.5% and one received oral acetazolamide [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…15 Topical brinzolamide 11 and its fixed combination with timolol 10 were found effective by Dayanir et al and Georgakopoulos et al, respectively. Furthermore, brimonidine was proved efficacious by Rainer et al, 14 Pharmakakis et al 9 proved the effectiveness of brimonidine-timolol eye drops solution and Scuderi et al 12 showed the effectiveness of topical apraclonidine. Topical timolol maleate controlled effectively postoperative IOP elevations as reported by Borazan et al 16 The aim of this study was to evaluate the efficacy of BBFC in preventing IOP elevation during the first 24 postoperative hours, in eyes that underwent uncomplicated phacoemulsification cataract surgery with Viscoat and Provisc as OVDs.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of several antiglaucoma drugs on IOP control following cataract surgery has been widely studied. [9][10][11][12][13][14][15][16] The first fixed combination of antiglaucomatic drugs without beta-blocker was approved recently for commercial use in Europe. Simbrinza (Alcon Pharma GmbH, Puurs, Belgium) consists of brinzolamide 1%, a carbonic anhydrase inhibitor, and brimonidine 0.2%, an α 2 -agonist.…”
Section: Introductionmentioning
confidence: 99%